Angkringan Terror Cafe Marketing Strategy According to the Sharia Concept - Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Research is For know management marketing on Angkringan Teror Cafe in Bendungan Village, Kulon Progo Regency and to find out the Islamic economic review of marketing The Angkringan . For reveal problem the in a manner deep And thorough, researcher use approach qualitative with technique collection data form interview Which deep on 20 respondent. By performing data analysis techniques that use inductive methods and descriptive analysis. From results study found results that Management Marketing on Angkringan Terror Cafe is by using 4P namely Product, price, place, Promotions. If the review is in accordance with the concept of sharia.